2005
DOI: 10.1097/00005082-200509001-00010
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Therapeutic Regimen in Heart, Lung, and Heart-Lung Transplant Recipients

Abstract: Optimal outcome after heart, lung, and heart-lung transplantation can only be obtained if patients are supported in adhering to a lifelong therapeutic regimen. The transplant patient's therapeutic regimen consists of a lifelong medication regimen, including immunosuppressive drugs; monitoring for signs and symptoms related to complications; avoidance of risk factors for cardiovascular disease and cancer (ie, diet and exercise prescriptions, nonsmoking); avoidance of abuse/dependence of alcohol or illegal drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 70 publications
2
103
0
3
Order By: Relevance
“…Although findings indicate the importance of anticipating the individual needs of each patient to enhance effectiveness, most current interventions fail to do so [19,20,48]. It has been suggested that variance in effectiveness of SMS could be due to the mismatch between the individual's needs and the offered intervention [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although findings indicate the importance of anticipating the individual needs of each patient to enhance effectiveness, most current interventions fail to do so [19,20,48]. It has been suggested that variance in effectiveness of SMS could be due to the mismatch between the individual's needs and the offered intervention [49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that psychosocial (e.g. depression, anxiety) and behavioral factors could negatively affect self-management and are therefore important targets for SMS interventions [19,20,48,50].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study of lung transplantation in children with CF failed to find systematic survival benefit in the United States (2). Nonadherence was not considered in that study, but it may play a role in the potential lack of survival benefit of lung transplantation in children (77)(78)(79)(80)(81).…”
Section: And W Van Der Bijmentioning
confidence: 99%
“…Reported nonadherence varies from 1 to 10% of patients after transplantation for substance use (tobacco, alcohol, illicit drugs) to 19 to 25% for nonadherence to immunosuppressants (79). Nonadherence rates varied substantially depending on the type of organ transplanted (78). Nonadherence for immunosuppressants was highest in kidney recipients (77).…”
Section: Nonadherencementioning
confidence: 99%
See 1 more Smart Citation